Helena Ferrari Teixeira: entre saberes e representações - Brancher, Vantoir Roberto (2006)
This dissertation inserts itself in the line of "Formation, knowledge and professional Development" in the PPGE - Program of Post-Graduation in Education of the UFSM - Federal University of Saint Maria. In this work, I considered myself to know the knowledge and the representations, of Helena Ferrari Teixeira, councilman and operating teacher in the decade of 40, in the city of Saint Maria. To know and to analyze the History of Life of this singular teacher, of significant importance for the History of the Women in Brazil, the Education and the Politics had been some of the objectives of this research. To (re)construct its History, I used the Biographical Method Histories of Life, in the Verbal modality, basing itself, also, in other forms of documentation such as periodicals, photographs, depositions and other carried through research already. Of this inquiry, first, had resulted some interviews with the main personage and the collaborators, who had passed for an analytical work, to the light of theoretical referential in the thematic of Sort, memory, Verbal History, Knowledge etc. The (re)construction of the Life History of Helena Ferrari Teixeira, the first woman in Santa Maria in Legislature, was realized also, through interviews with five of its former-pupils. I found in the familiar and/or public archives a significant number of documents and photographs of the teacher, which minutely had been also systemized by me. My work was finished with the production of this composed dissertation for five chapters where, at a first moment, I present the ways that I covered for the arrival to the searched subject, later, I talk with some authors, demonstrating the reason of determined choices in the collection and analysis of the data and in the proper construction of the work. In the following chapter I pass through the quarrel of [re]construction of Histories of Life, having as collaborating and citizen-source people of the third age. And, the sequential chapters, I went deep in the History of Life, properly said, of Helena Ferrari Teixeira, composing this production through its own staffs and professionals. Being thus, I believe that to the look to the knowledge of the professors of a time provided to me to a new signification of other times and lived spaces and meanings for me today. From this, I believe that, looking at the daily knowledge of the professors can, and is, showing itself as one more excellent alternative in the production and/or new signification of the professors knowledge and practical.